Living Hadis di Era Digital: Konsistensi Keberagamaan dan Adaptasi Media dalam Praktik Tradisi Kenabian Jama'ah Tabligh - Ahmad Al Haitami; Hakami Mundziri Sastra (Journal of Hadith Studies, 2025)
This study examines the practice of living hadith within the Jamaah Tabligh (JT) movement, positioning it as a religious actor undergoing transformation in the digital sphere, particularly through the platform YouTube. Theoretically, the study is grounded in the question of how hadith, traditionally embodied through oral transmission, face-to-face interaction, and collective spiritual formation, is re-mediated within the ecosystem of digital media. It aims to analyze patterns of hadith representation, shifts in the structure of religious authority, and the theological as well as social implications of the digitalization of JT’s da‘wah activities. This research employs a qualitative approach, combining digital ethnography with content analysis. Data were collected through online observation of sermon videos on the “Jamaah Tablig Dunia” channel, along with analysis of audience interactions in the comment sections as sites for negotiating meaning and legitimizing authority. The findings indicate that JT’s presence on YouTube does not merely relocate conventional preaching into a new medium; rather, it reconfigures the modes through which hadith is presented and authorized. Hadith continues to function as a form of practical pedagogy internalized through collective discipline rather than as an object of textual-critical inquiry. Nevertheless, digital mediation shifts the basis of authority from embodied relationships to forms grounded in visuality, channel legitimacy, and platform algorithmic logic. This adaptation preserves theological substance while generating new dynamics between tradition and digital media rationality in contemporary Islamic practice.